NIMG-40. RAPID EARLY PROGRESSION (REP) OF GLIOBLASTOMA IS AN INDEPENDENT NEGATIVE PROGNOSTIC FACTOR: RESULTS FROM A SYSTEMATIC REVIEW AND META-ANALYSIS. (14th November 2022) - Waqar, Mueez; Roncaroli, Federico; Lehrer, Eric; Palmer, Joshua; Villanueva-Meyer, Javier; Braunstein, Steve; Hall, Emma; Aznar, Marianne; De Hamer, Philip Witt; D'Urso, Pietro; Trifiletti, Daniel; Quiñones-Hinojosa, Alfredo; et al.
Abstract: INTRODUCTION: In patients with newly-diagnosed glioblastoma, rapid early progression (REP) refers to tumour regrowth between surgery and postoperative chemoradiotherapy. This systematic review and meta-analysis appraised published data on REP to better characterise and understand it. METHODS: Systematic searches of MEDLINE, EMBASE and the Cochrane database from inception to 21/10/21. Studies describing the incidence of REP – tumour growth between the postoperative MRI scan and pre-radiotherapy MRI scan in newly-diagnosed glioblastoma, were included. The primary outcome was REP incidence. RESULTS: From 1590 search results, 9 studies were included with 716 patients. The median age was 56.9 years (IQR 54.0-58.8 years). There was a male predominance with a median male-to-female ratio of 1.4 (IQR 1.1-1.5). The median number of days between MRI scans was 34 days (IQR 18-45 days). The mean incidence rate of REP was 45.9% (range 19.3%-72.0%) and significantly lower in studies employing functional imaging to define REP (p< 0.001). REP/non-REP groups were comparable with respect to age (p=0.99), gender (p=0.33) and time between scans (p=0.81). REP was associated with shortened overall survival (HR 1.78, 95% CI 1.30-2.43, p< 0.001), shortened progression-free survival (HR 1.78, 95% CI 1.30-2.43, p< 0.001), subtotal resection (OR 6.96, 95% CI 4-51-10.73, p< 0.001) and IDH wildtype versus mutant tumours (OR 0.20, 95% CI 0.02-0.38, p=0.03). MGMT promoter methylation was not associated with REP (OR 1.29, 95% CI 0.72-2.28, p=0.39). CONCLUSIONS: REP occurs in almost half of patients with newly-diagnosed glioblastoma and has a strongly negative prognostic effect. Future studies should investigate its biology and effective treatment strategies.